Formation of Students' Readiness for Professional Design and Construction Activities Based on an Integrative Approach - Zh. О. Khakimov; F. M. Rakhmatova (Цифровая трансформация)
The approach, stages, criteria and levels of development of design and engineering competencies among bachelors in technical areas of study are presented as an integral, multi-level dynamic system, as well as didactic components of the educational process. The proposed approach is based on the continuity of the process of preparing students for design and engineering activities throughout the entire period of study at the university, on the use of problem-oriented and designed teaching principles, along with the interdisciplinary nature of education and leading independent work.